Knowledge, attitude, practices, awareness, and confidence (KAPAC) among general dental practitioners on basic periodontal examination (BPE) - Nur Zety Mohd Noh; Wan Nur Syamimie Wan Ismail; Wan Nur Izzati Wan Maznan; Sobrina Mohamed Khazin; Yunita Dewi Ardini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: General dental practitioners (GDP) are responsible for providing new patients with periodontal screening. However, the knowledge, attitude, practices, awareness, and confidence (KAPAC) of GDP in performing basic periodontal examination (BPE) are still unclear. Purpose: This study identified the KAPAC towards performing BPE among GDP. Methods: A cross-sectional study was conducted using a self-administered questionnaire, distributed online to Malaysian GDP. The questionnaire consisted of six sections: respondents’ demographics, knowledge, attitude, practices, awareness, and confidence in performing BPE. Data were analysed descriptively and Spearman’s correlation coefficient test was employed to determine the correlation between knowledge, attitude and practices towards awareness and confidence. Results: A total of 137 GDP responded to the questionnaire. Majority of respondents demonstrated good knowledge (73.0%), positive attitude (89.8%) and good practices (75.0%) towards performing BPE. Only 66.4% and 51.8% of respondents had high awareness and confidence, respectively. The knowledge and practices of BPE showed a weak positive correlation (p<0.05) with awareness and confidence in performing BPE, with correlation coefficients ranging from r=0.211 to r=0.346. Conclusion: A moderate to good level of KAPAC is found among GDP towards BPE. Patient oral health outcomes would benefit from a greater focus on periodontal screening education and practice. Further emphasis should be placed on the importance of periodontal screenings for patient care.